Feasibility And Efficiency Of Ureterorenoscopy As A Day-care Procedure For Treatment Of Ureteric Calculi - Haroon Sabir Khan; Hussain Ahmed; Mobashir Ahmed Saeed; Muhammad Akmal; Muhammad Nawaz; Mudassar Sajjad (Journal of Bahria University Medical and Dental College)
Objective: To assess the feasibility and efficiency of ureterorenoscopy as a day-care procedure for treatment of ureteric calculi in order to reduce their heavy workload and to spare resources for reducing long waiting list of elective advanced urological surgeries for patients admitted as an indoor category. Study design: Prospective descriptive study. Place and duration of study: The study was conducted in Urology department of PNS Shifa, Karachi from July 2017 to March 2018. Methodology: All patients who presented to our institute for ureteric calculi with normal creatinine and no urosepsis were included in the study. The ureterorenoscopy procedure was carried out either in spinal anesthesia or general anesthesia using laryngeal mask. Post-operative outcomes criteria for feasibility were assessed as ‘rate of complications that required admission in the hospital’. Results: A total of 164 patients underwent ureterorenoscopy. Out of these 151 successful ureterorenoscopy procedures for urolithiasis were performed with 98% stone clearance. Majority of patients went home the same day with no sequel, only twelve patients were kept for a day or two for minor complications. Nine of these had severe pain postoperatively requiring parenteral analgesia and were discharged on first postop day. Three had developed fever and were discharged on second postop day. No confounding factors were found to predict the readmission event. Conclusion: A day care ureterorenoscopy is a safe procedure in a full time day care setting, with a rapid turnover and clinically safe outcome with few and trivial complications requiring readmission.